Hubungan Karakteristik Konsumen dan Keputusan Pembelian Daging Ayam di Pasar Modern Kota Pontianak - Kusumawati, Ely Marini; Kurniati, Dewi; Maswadi, Maswadi (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
As Indonesia's economy continues to grow, the poultry industry is expected to adapt and innovate to meet the increasing demand. This research aims to analyze the relationship between consumer characteristics and purchasing decisions regarding chicken meat in modern markets. A qualitative descriptive approach was employed to elucidate the research findings, utilizing data from 120 respondents analyzed through Spearman rank correlation. The results indicate that the variables of education level, type of occupation, and income level are significantly correlated with purchasing decisions for chicken meat products in modern markets, exhibiting a positive relationship. These findings suggest that consumers with higher incomes, specific types of occupations, and better education are more inclined to prefer high-quality chicken meat in modern markets.